=-6(h+3)-8(h-7)

Simple and best practice solution for =-6(h+3)-8(h-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =-6(h+3)-8(h-7) equation:


Simplifying
0 = -6(h + 3) + -8(h + -7)

Reorder the terms:
0 = -6(3 + h) + -8(h + -7)
0 = (3 * -6 + h * -6) + -8(h + -7)
0 = (-18 + -6h) + -8(h + -7)

Reorder the terms:
0 = -18 + -6h + -8(-7 + h)
0 = -18 + -6h + (-7 * -8 + h * -8)
0 = -18 + -6h + (56 + -8h)

Reorder the terms:
0 = -18 + 56 + -6h + -8h

Combine like terms: -18 + 56 = 38
0 = 38 + -6h + -8h

Combine like terms: -6h + -8h = -14h
0 = 38 + -14h

Solving
0 = 38 + -14h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '14h' to each side of the equation.
0 + 14h = 38 + -14h + 14h
Remove the zero:
14h = 38 + -14h + 14h

Combine like terms: -14h + 14h = 0
14h = 38 + 0
14h = 38

Divide each side by '14'.
h = 2.714285714

Simplifying
h = 2.714285714

See similar equations:

| 106=6x+4(-3x+34) | | 1/3x^(2/3) | | 14x+30=12x-58 | | 0=1/3x^2/3 | | 5x+18=34 | | 0=-2(x-1) | | 2y=500-2x | | 2x=500-2y | | 132=-50-7x | | 0=2(x+2) | | 3.2x+2.3=-9.4 | | 9x-7=3x+12 | | abs(6x)-4=0 | | 8x-12=x+10 | | -14=x/2-6 | | x+x+y+y=500 | | 17=2s+1 | | -x+188=-436+15x | | 4hsquared-2h(h-2)= | | 3tg^2(5x)-9=0 | | 10x-15=9x+3 | | =-14g-21+24g+16 | | 3n+10=n-7 | | =7(-2g-3)+8(3g-2) | | -12(-8x-39)=-588 | | 2m-55n7/14m6n3 | | 2.3x*3.2=-9.4 | | -3(y-2y)+4=-3(2y-y)+8+5y | | -5+55=55 | | 50+2g=7g | | 9x^2+3x+25=11 | | (x+2)(2x-3)=x+26 |

Equations solver categories